Co3O4 nanocrystals coupled with O- and N-doped carbon nanoweb as a synergistic catalyst for hybrid Li-air batteries. (March 2015) - Li, Longjun; Liu, Siyang; Manthiram, Arumugam
Abstract: Expensive Pt-based catalysts are usually required to achieve a high discharge voltage and long operation life for hybrid Li-air batteries. However, the cost of the catalysts needs to be lowered by either reducing the Pt loading in the catalysts or replacing Pt with less expensive catalysts. Here, we report the strong coupling of Co3 O4 nanocrystals with an O- and N-doped carbon nanoweb (ON-CNW) as a low-cost, highly-efficient catalyst for hybrid Li-air batteries with an alkaline catholyte. Co3 O4 /ON-CNW greatly reduces the discharge overpotential compared to ON-CNW and exhibits longer cycle life, which is even better than that of the best reported N-doped mesoporous carbon (0.016% decrease in efficiency per cycle for 130 cycles compared to 0.017% decrease per cycle for 100 cycles obtained with N-doped mesoporous carbon). Although Pt/C exhibits a slightly higher initial discharge voltage (3.02 V compared to 3.00 V for Co3 O4 /ON-CNW), the cycle life of Pt/C is<50 cycles, making Co3 O4 /ON-CNW as a viable, stable cathode for hybrid Li-air batteries. Graphical abstract: Co3 O4 nanocrystals strongly coupled with O- and N-doped carbon nanoweb (Co3 O4 /ON-CNW) have been developed as an efficient, non-noble-metal oxygen reduction reaction (ORR) catalyst for hybrid Li-air batteries. Highlights: Co3 O4 nanoparticles are deposited onto O- and N-doped carbon nanoweb as a catalyst. Synergistic catalytic effect arises from the strong coupling between Co3 O4 and carbon. The catalytic activity is similar to Pt/C but with better durability. The hybrid catalyst enables long-life hybrid Li-air cells with little degradation.